Late quaternary alluvial history of the Brazos River in central Texas. (10th September 2022) - Taormina, Rebecca; Nordt, Lee; Bateman, Mark
Abstract: The late Quaternary history of the bedrock-controlled Brazos River system in central Texas is poorly understood as to the complex interplay between bedrock and climate on episodes of channel incision and aggradation. Through geomorphic assessment, sediment core analysis, and luminescence dating (OSL) we map the alluvial terrace and floodplain deposits in the Steinbeck Bend study area in central Texas. Five stratigraphic (allostratigraphic) units were identified beneath four alluvial terrace-sediment complexes (T3-Unit I, T2a-Unit II, T2b-Unit III, T1a-Unit IV, T1b-Unit V) and the current floodplain (T0-Unit VI) of the Brazos River, with the accompanying OSL geochronology ranging from >60 to 0.3 ka. Channel incision appears to have occurred during the transition to cooler and wetter intervals at the beginning of MIS 4 and MIS 2. Alluvial deposition proceeded mainly during the latter stages of the warmer MIS 5 and during the first half of MIS 3, both characterized by a slight warming trend. The alluvial architecture of all units was formed by single story, mixed load meandering channels migrating laterally across Cretaceous marls. Upstream from the study area, the bedrock valley narrows because of the presence of more resistant limestones forming the bedrock channel floor and valley walls. In the Steinbeck Bend study area, the incised meanders develop into larger radius of curvatures as the Brazos River migrates across less resistant Cretaceous marls. Below the study area in the weakly consolidated Tertiary coastal plain deposits, the Brazos River becomes freely meandering, cutting laterally and vertically through previously deposited alluvium interceded by channel avulsions.